Analisis Perbandingan Kinerja Keuangan pada PT Bank Central Asia Tbk Sebelum dan Sesudah Akuisisi PT Bank Interim Indonesia (PT Bank Rabobank International Indonesia) - Mafiana, Della; Murwanti, Sri (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Financial ratios including CAR, ROA, ROE, NIM, BOPO, and LDR were used in this study to see if there were any changes in the company's financial performance between the pre- and post-acquisition periods of PT Bank Interim Indonesia (PT Bank Rabobank International Indonesia). With a comparative research design, this study falls within the quantitative research category. Secondary data for the five-year period (2018–2022) was obtained from PT Bank Central Asia Tbk's quarterly financial filings. With the use of SPSS software, the paired sample t-test and the Wilcoxon test are the data analysis techniques performed. The paired sample t-test produced the following output, the CAR and LDR variables showed significant differences, while the other two ROA and ROE variables did not have differences in the period before and after the acquisition. The other two variables, NIM and BOPO were tested using the wilcoxon test and the output of the NIM variable showed a significant difference, while the BOPO variable did not have any difference in the period before and after the acquisition.